The effects of two fixation methods on blood loss in patients with trochanteric fracture: dynamic hip screw vs. proximal femoral nail anti-rotation - Mirza Sivro; Faruk Lazović; Ðemil Omerović; Adnan Papović (Medicinski glasnik, 2023)
Aim: The two most commonly used implants for treatment of trochanteric fractures are the dynamic hip screw (DHS) and proximal femoral nail antirotation (PFNA). The aim of this study was to evaluate blood loss in patients with trochanteric fracture treated with DHS or PFNA. Methods: This retrospective comparative study included 61 patients with trochanteric fracture, who were divided according to a surgical method into DHS and PFNA groups. In the PFNA group, a short third generation gamma-nail was used for osteosynthesis (Supernail GT, Lima Corporate, Italy), and in the DHS group a dynamic hip screw was used (Synthes, Oberdorf, Switzerland). Complete blood count with haemoglobin and haematocrit values was taken preoperatively and on the first day postoperatively and a number of red blood cell transfusions (RBC) were evaluated. Electronic medical records from 2022 were used to collect patient data. Results: There were no significant differences in terms of gender and age between the groups (p=0.510 and p=0.087, respectively), as well as in the fracture type distribution (p=0.886). The duration of postoperative hospitalisation was similar between the groups (p=0.643). There was no statistically significant association between the number of RBC transfusions and fixation method (p=0.091), as well as in postoperative haemoglobin and haematocrit levels between the groups (p=0.180 and p=0.225, respectively). Conclusion: Both DHS and PFNA implants are safe surgical techniques for the treatment of trochanteric fractures, with similar blood loss, number of blood transfusions and hospital stay.
Keywords: haemorrhage; intramedullary nailing; sliding hip screw; trochanteric fractures